Conflito e violência na escola de educação básica: análises de teses em educação no Brasil de 1999 a 2016 - Cardozo, Sandra Moraes da Silva (2019)
This study analyzed PhD dissertations produced in Education Graduate Programs in Brazil, from 1999 to 2016, on the issue of conflicts and school violence in the context of Basic Education. The goal of this research was to analyze the main contributions of works on conflicts and school violence in basic education, identifying the factors that favor a respectful coexistence and the obstacles that impede the construction of respectful relationships in the context of basic education. In addition, this research aimed to relate the results of these dissertations with Freire’s (1981, 1995, 2000, 2014) inter-relational categories of deliberative dialogic practice, Habermas’s (2002, 2012) view on people inclusion and Sen’s (2010) take expansion of the liberties for the verification of proximity and distancing. The data collection was focused on the databases of the indexing platform of the Coordination of Improvement of Higher Education Personnel (CAPES). The temporal period of the research was methodologically delimited to encompass a broader scenario on the topic of the study. The research was bibliographic. Our approach was qualitative and quantitative, supported by the content analysis, statistical probabilistic analysis and the principles of critical communicative methodology. 64 theses were collected on CAPES indexing platform, using the inclusion and exclusion criteria defined in the study. We had access to only 56 PhD dissertations. The theoretical fundamentals were based on the contributions of Freire (1981, 1995, 2000, 2014), Habermas (1987, 2002, 2012) and Sen (2010) on school conflicts and violence. The results highlight that the most effective mediations are those based on democratic and dialogical deliberative practices in which the whole school community becomes representative in decisions and deliberations and is free to expand its capacities of action and communication in the educational act. Authoritative and coercive practices are more harmful and impair educational and pedagogical interactions in schools and feedback on violent practices. We propose an analytical strategy to evaluate the relevance of research in the context of basic education from the historical categories "denunciation/annunciation" in Freire (1981, 1995, 2000, 2014) and the interrelated categories "dialogic deliberative practice" and " people inclusion" in Habermas (2002 and 2012) and "expansion of freedoms" in Sen (2010). We believe that the categories in Freire (1981, 1995, 2000, 2014), Habermas (2002 and 2012) and Sen (2010) can may be used to evaluate and validate actions in school aimed at overcoming violence and conflict mediations.